1994
DOI: 10.1038/ki.1994.297
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma levels in peritoneal dialysis effluents: Relation to peritonitis

Abstract: As peritoneal macrophages require Interferon-gamma (IFN-gamma) for bacterial lysis, IFN-gamma levels were measured in peritoneal dialysis effluents. (PDE) by a specific radioimmunoassay. High IFN-gamma levels were found in patients with peritonitis compared to low levels in patients without peritonitis (mean 9.73 +/- 2.63 SE U/ml, N = 39 vs. 0.25 +/- 0.04, N = 32). IFN-gamma levels varied among different bacteria: Staph. aureus (highest: 23.4 +/- 5.7, N = 14), Staph. epidermidis (lower: 3.2 +/- 0.8, N = 13), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…A broad spectrum of effects exerted by lymphocyte-derived mediator IFN-␥ (12) points to a significant role of lymphocytes in the inflammatory response. In this respect, increased levels of IFN-␥ have been detected in the inflamed peritoneum, and this rise has been clearly attributed to peritoneal lymphocytes (13).…”
Section: :Cd8mentioning
confidence: 90%
“…A broad spectrum of effects exerted by lymphocyte-derived mediator IFN-␥ (12) points to a significant role of lymphocytes in the inflammatory response. In this respect, increased levels of IFN-␥ have been detected in the inflamed peritoneum, and this rise has been clearly attributed to peritoneal lymphocytes (13).…”
Section: :Cd8mentioning
confidence: 90%
“…Second, the presence of this population provides a unique experimental setting to study DC biology especially as it relates to in vivo and in situ differentiation of these cells. Previous studies have shown that PD-related peritonitis correlates with increased levels of IFN-g levels in the peritoneal effluent, implying that the predominant adaptive immune response to peritoneal infection is cell-mediated [14,15]. DC play a critical role in the initiation of such a response by uptaking antigens from the aetiological pathogen and subsequently migrating to nearby secondary lymphoid tissues to activate T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we demonstrate that the entire peritoneal pool of CD14 + mononuclear cells have the capacity to differentiate into DC or macrophages in vitro , under appropriate conditions, indicating that these cells are not fully differentiated despite their location in peripheral tissues. These data provide a mechanistic explanation for the predominant Th1 environment observed during episodes of PD-related peritonitis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…We have examined the regulatory effects of IFN-␥ on constitutive as well as proinflammatory cytokine (IL-1␤ and TNF-␣)-induced HPMC-chemokine production with doses of cytokines known to be present in the peritoneal cavity during bacterial peritonitis (14,15). Our in vitro culture studies show that IFN-␥ alone was an efficient stimulus for MCP-1 production, and the combination of IFN-␥ with IL-1␤ (or TNF-␣) resulted in significant synergistic up-regulation of MCP-1 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…cytokine levels during peritoneal dialysis-associated peritonitis suggests that i.p. elevation of the T cell-derived cytokines IFN-␥, IL-2, and IL-10 occur during infection (14,15). Recent in vitro studies indicate that IFN-␥ is capable of modulating both CXC and CC chemokine secretion in a number of cell types, data that suggest that it plays a central role in controlling leukocyte influx (16 -18).…”
mentioning
confidence: 99%